Green innovation and environmental quality in Regional Comprehensive Economic Partnership (RCEP) countries: moderating effect of institutional quality - Hamzah, Hanny Zurina; Wei, Zhai; W. Mohamad, Wan Norhidayah (Human Resource Management Academic Research Society, 2024)
This study examines the role of institutional quality in the relationship between green innovation and environmental quality in RCEP countries, using a panel dataset covering the period from 2000 to 2021. Through two-way fixed effects (TWFE) estimation, the analysis reveals that green innovation significantly reduces carbon dioxide emissions, with institutional quality amplifying its environmental benefits by supporting the implementation of green technologies. Countries with higher institutional quality are able to utilize resources more efficiently, resulting in substantial pollution reduction. Robustness tests confirm these findings, underscoring the importance of a strong governance framework for maximizing the environmental potential of green innovation. These insights highlight the need for institutional reforms and strategic policy support in RCEP countries to promote sustainable development, providing valuable guidance for policymakers.